Functional and radiological comparison of single or dual plate application in bicondylar tibia plateau fractures - (:unkn) unknown (My University, 2017)
Despite advances in operation techniques and implant techno- logy, there is still no consensus on both preoperative planning and postoperative follow-up of tibial plateau fractures. The aim of this study is to evaluate the functional results of bicondylar tibia plateau fractured patients treated in Ankara Numune Tra- ining and Research Hospital Orthopedic Clinic both from clinical and radiological aspects. The median follow-up period of 24 ret- rospectively determined patients was 33.1 months. Patients were divided into two groups as patients with single or double plates. Demographic characteristics of the two groups, fracture mecha- nisms and fracture types were determined. Functional outcomes were determined by using Rasmussen clinical and radiological scoring systems. There was no functional or radiological differen- ce between the two groups (p>0.05). Rasmussen clinical scores and radiological scores were found to be statistically compatib- le (p=0.001). Both surgical techniques can be used as an option in bicondylar tibia plateau fractures. However, in patients with double plates, soft tissue infection was seen more frequently, whereas in patients who only have lateral plate, more frequently seen collapses on the joint surface may affect surgical preferen- ces. Detailed clinical and radiological analysis and preoperative planning are crucial in determining the appropriate surgical tech- nique so that the expected functional results can be obtained.

Operasyon tekniklerindeki ve implant teknolojisindeki ilerleme- lere rağmen, tibia plato kırıklarının hem tedavi öncesi planla- ması hem de tedavi sonrasındaki takibi konusunda halen görüş birliği bulunmamaktadır. Bu çalışmanın amacı, Ankara Numune Eğitim ve Araştırma Hastanesi Ortopedi Kliniğinde tedavi edilen bikondiler tibia plato kırıklı hastaların klinik ve radyolojik olarak fonksiyonel sonuçlarının değerlendirilmesidir. Retrospektif olarak belirlenen 24 hastanın ortalama takip süresi 33,1 ay olarak be- lirlendi. Hastalar tek plak veya çift plak uygulananlar olarak iki gruba ayrıldı. İki grubun demografik özellikleri, kırık oluşum me- kanizmaları ve kırık tipleri belirlendi. Fonksiyonel sonuçlar, Ras- mussen klinik ve radyolojik skorlama sistemleri kullanılarak tespit edildi. Gruplar arasında fonksiyonel ve radyolojik olarak fark ol- madığı bulundu (p>0,05). Rasmussen klinik skorları ile radyolojik skorları arasında istatistiksel olarak uyum tespit edildi (p=0,001). Her iki cerrahi teknik de bikondiler tibia plato kırıklarında uygun seçenek olarak kullanılabilir. Ancak çift plak uygulanan hastalar- da yumuşak doku enfeksiyonu daha fazla görülmüşken, yalnızca lateral plak uygulanan hastalarda da eklem yüzeyinde çökmenin daha fazla görülmesi cerrahi seçenekleri etkileyebilir. Beklenilen fonksiyonel sonuçların elde edilebilmesi için, detaylı klinik ve rad- yolojik analiz ile preoperatif planlama, uygun cerrahi tekniğin belirlenmesinde büyük önem taşımaktadır.
Bikondiler tibia plato kırıklarında tek veya çift plak uygulamasının fonksiyonel ve radyolojik olarak karşılaştırması
Keywords: Genel ve Dahili Tıp